Nodular Elastosis of the Pancreas - Whitney Wedel; Geoffrey Talmon; Aaron Sasson (Case Reports in Pathology)
Elastofibromatous change is a benign process that has been increasingly recognized in the tubular gastrointestinal tract. These changes can present as a colonic polyp or be seen in conjunction with inflammatory changes. Similar lesions have been noted in the liver, apparently associated with vascular injury. We describe a case in which multiple circumscribed nodules of elastofibromatous change within the pancreas had a similar morphology to nodular elastosis of the liver. To our knowledge, this is the first description of such a finding occurring within the pancreas.